Pemberdayaan Pengelolaan Keuangan Masjid Berbasis Kotak Amal Transparable Masjid Al-Mujahidin Desa Sukasari Kabupaten Seluma - Hanif, Padlim; Auliya, Zahroh; Marlina, Reni; Ermaroutul Fuaddah, Fitri; Retno Sari, Yosi; Nurul Hidayah, Kharisma; Juniarsih, Nosin; Natalia, Kurnia; Saputra, Riki; Rahman Lubis, Abdul; Ugra, Seprian (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This service aims to provide knowledge about the dimensions of Accountability and Transparency of financial management in the Al-Mujahidin Mosque and to provide more comprehensive knowledge to the management of the Al-Mujahidin Mosque in managing financial reports. The service method used is to use a mentoring-based approach. The results of the service show that there is a semiotic dimension for the management and congregation of the Al-Mujahidin Mosque to apply the principles of Transparency and Accountability in managing mosque finances starting from the use of available charity boxes.